Measurement of stress evolution in pulse-reverse electrochemical deposition using Micro-Raman Spectroscopy - Yang, Qi Hua (2011)
Nowadays, copper deposit is extensively used in microelectronic applications, because the electroplated copper exhibits excellent electrical conductivity along with high hardness. in the resent literature, it is known that copper electroplated with pulse reverse current produces larger hardness than that by DC (direct current) plating or PC (pulse current)plating.